Genomic signatures of artificial selection in fecundity of Pacific white shrimp, Penaeus vannamei - Sui, Juan; Luan, Sheng; Cao, Jiawang; Dai, Ping; Meng, Xianhong; Luo, Kun; Chen, Baolong; Tan, Jian; Fu, Qiang; Kong, Jie (Frontiers in Genetics, 2022)
Penaeusvannamei is the most important economic shrimp in the world. Many selective breeding programs are carried out to improve its production and performance traits. Although significant differences in the reproductive ability of female P. vannamei under artificial breeding conditions have been reported, the genome-wide adaption of the reproductive ability of domesticated female P. vannamei is less investigated. In this study, whole-genome analysis was performed along with pooled DNA sequencing on two fecundity separated bulks, high fecundity bulk (HB), and low fecundity bulk (LB). Each bulk contained 30 individuals from 3 commercial populations. A sequencing depth of >30× was achieved for each bulk, leading to the identification of 625,181 and 629,748 single nucleotide polymorphisms (SNPs) in HB and LB, respectively. Fixation index (Fst) combined with p ratio allowed for the identification of 145 selective sweep regions, with a sequence length of 14.5 Mb, accounting for 0.59% of the genome. Among the 145 selective sweep regions, a total of 64,046 SNPs were identified, and further verification was performed by genotyping 50 candidate SNPs on 60 samples from the offspring of the three populations. Furthermore, 121 genes were screened from the sweep regions. GO annotation and KEGG enrichment analyses showed that partial genes were essential for fecundity regulation. This study provides important information for in-depth investigation of genomic characteristics for long-term selective breeding on the fecundity of female P. vannamei and will also be important for genome-assisted breeding of P. vannamei in the future.